A serine loop in tissue factor mediates substrate selectivity by the tissue factor – factor VIIa complex - Birkle, Fabienne (J Thromb Haemost, 2020)
BACKGROUND: The tissue factor – factor VIIa (TF-FVIIa) complex is the physiologic activator of blood clotting and plays a major role in many thrombotic diseases. TF-FVIIa drives clotting through proteolytic cleavage of its major protein substrates, factor IX (FIX) and factor X (FX). However, it remains unclear how TF-FVIIa exhibits selectivity between these substrates. We previously showed that TF residues adjacent to the putative substrate binding site of TF (“exosite”) facilitate FX activation, but the role of these residues in substrate selectivity had not been tested. OBJECTIVES: We hypothesized that a TF serine loop (residues S160-S163) mediates substrate selectivity by the TF-FVIIa complex. METHODS: We generated TF serine loop and exosite mutants. The mutants were tested in FIX and FX enzyme activation assays as well as thrombin generation assays. RESULTS: Changes in the length of the serine loop affected rates of FIX and FX activation very differently. FX activation was decreased by up to 200-fold when the loop length was changed by just one residue. In contrast, FIX activation was largely unaffected. Substrate selectivity was also detected in thrombin generation assays. Activation assays with TF serine loop and exosite double mutants revealed that the serine loop has no effect on the exosite during FIX activation. In contrast, the serine loop regulates the exosite during FX activation. CONCLUSIONS: Our results provide new insights into how the TF-FVIIa complex actively selects between its major protein substrates, which is mediated by a TF serine loop.